Roots in the air : a philosophical autobiography of a philosopher, artist, and musician - Krausz, Michael, 1942- (Value Inquiry Book Series, 2018)
By way of dialogues, Michael Krausz offers philosophical reflections about his life as philosopher, artist, and musician. He also rehearses his views about relativism, interpretation, creativity, and self-realization. Much of Krausz's work has been inspired by conversations with thinkers such as Karl Popper, Thomas Kuhn, Isaiah Berlin, the Dalai Lama, and musicians such as Josef Gingold, Frederik Prausnitz, and Luis Biava. While the death of his grandparents in Auschwitz continues to disquiet his consciousness, Krausz's critiques of versions of Advaitic Hinduism and Tibetan Buddhism led him to a distinctive humanism. This thought-provoking book includes personal and professional accounts about particular philosophers, artists, and musicians. It will edify anyone who, like Krausz, has confronted issues of self-identity and human existence.